A Study of Mae Sot’s Identity to develop Tourism Product in Mae Sot Municipality, Tak Province - Sainaratchai, Krittika; Kieanwatana, Komsit (Journal of Cultural Approach, 2020)
The purposes of this research were to study and explore Mae Sot’s Identity to develop Tourism Product in Mae Sot Municipality, Tak Province. This is qualitative research using focus group discussion, and in-depth interviews. The researchers collected data from specialists in Mae Sot Municipality officer, tourism industry, tourism product, and souvenir enterprise in Mae Sot Municipality, Tak Province. Results of the study showed that the distinctive identity of Mae Sot is the center of an ethnically diverse society. This place combines an interesting lifestyle, arts, and culture. Moreover, this area also offers tourism products that should be promoted and developed along with a creative tourism route. The objective of this route was to learn the identity of Mae Sot about ethnic groups of local people through the participation in their activities about lifestyle and the production of their well - known goods. For examples, souvenirs include wood product, jewelry, especially, tribal fabrics which are unique to Mae Sot, and agricultural products. These fabrics should be fully promoted and developed in design to present the local wisdom and uniqueness of each tribe and ethnicity. They include a mix of tribal and ethnic diversity to create new fabric products and to promote the ethnic and tribal souvenir products of Mae Sot to become a significant souvenir and tourism product, unique and the identity of Mae Sot.